Air Pollution and Urban Environment: Residents Approach in the Wider Area of Volos City, Greece - Louisa Skylodimou; Paschalina Lytoudi; Theodore Metaxas (Urban Science)
Air pollution in urban environments is a complex, multidimensional issue that significantly impacts public health and people’s well-being. Previous studies have tended to focus on general public awareness in metropolitan urban areas. The novelty of this study lies in examining whether perceptions regarding air pollution and the urban environment differ based on specific demographic characteristics such as age and dwelling place in a provincial city of Greece. Thus, a quantitative cross-sectional research approach was employed, resulting in the collection of 659 valid questionnaires from residents in the wider area of Volos city. To analyze the data, one-way ANOVA was applied to reveal differences in perceptions of air pollution and its effects on urban well-being. The results indicate that perceptions vary by age, particularly concerning the effects of air pollution on the natural environment. Participants acknowledge that air pollution levels differ across cities of various sizes and recognize the adverse effects of pollution on the overall well-being of urban areas. Furthermore, our analysis reveals significant differences in perceptions between urban and rural residents. Particularly, people living in the city tend to report higher awareness of air pollution levels compared to those in the countryside, highlighting the need for targeted interventions tailored to specific communities. Overall, this study underscores the importance of understanding demographic influences on perceptions of air quality, which can inform policymaking and public health initiatives aimed at improving air quality and mitigating health risks in urban settings.